Preparation of Thin Film CuSnO3 by Dip Coating Method: Structural, Optical, and Electrical Properties for Dye-Sensitized Solar Cell Applications - Hary Sanjaya; Hermansyah Aziz; Yeni Stiadi; Syukri Arief; Yohandri Yohandri; Septian Budiman (Department of Chemistry, Faculty of Science and Technology Syarif Hidayatullah Jakarta State Islamic University, 2026)
This study addresses the critical need for cost-effective, earth-abundant alternatives to Indium Tin Oxide (ITO) by developing transparent and conductive Copper Stannate (CuSnO₃) thin films via sol-gel dip-coating. Using diethanolamine (DEA) and monoethanolamine (MEA) as chelating agents to enhance film stability and uniformity, the synthesized films were calcined at 550 °C, yielding predominantly amorphous structures that minimize grain boundary recombination. Characterization revealed crack-free morphologies with a thickness of approximately 1.88 μm, while optical analysis showed band gap energies ranging from 2.16 eV (DEA) to 2.31 eV (MEA), suitable for visible-light absorption. Electrical measurements indicated significant improvements in conductivity, with MEA-modified films achieving 173.58 S/m and DEA-modified films reaching 3600 S/m.When used as photoelectrodes in Dye-Sensitized Solar Cells (DSSCs) with natural sensitizers, the films demonstrated successful photovoltaic performance, with Quercetin yielding the highest power conversion efficiency of 0.26%, thereby validating solution-processed amorphous CuSnO₃ as a viable, low-cost material for scalable optoelectronic applications.